Biosynthetic production of human growth hormone gene in methylotrophic yeast, Pichia pastoris - Loh, Danley; Muhammad, Tengku Sifzizul Tengku; Najimudin, Nazalan; Arip, Yahya Mat; Samian, Mohd Razip (Penerbit Universiti Sains Malaysia, 2004)
Human growth hormone (hGH) is secreted from the anterior pituitary gland and exerts a wide variety of functions such as, IGF-1 production, protein synthesis, glucose metabolism, lipolysis, lipogenesis, and cell proliferation/differentiation (Isaksson et al., 1985; Press, 1988; Thorner and Vance, 1988; Strobl and Thomas, 1994).